How to Assess Drugs in the Treatment of Acute Bipolar Mania? - Bourin, Michel; Thibaut, Florence (Frontiers in Pharmacology, 2013)
Bipolar affective disorder is a serious mental disease associated with significant morbidity and mortality. Good-quality research available to guide treatment strategies remains insufficient, particularly with regard to manic or hypomanic episodes. A critical review of the various stages of mania might be helpful for pharmaceutical companies and investigators as a prerequisite for the clinical evaluation of potential antimanic properties of medications. The main difficulty is with a comparison between anticonvulsants, antipsychotics, and mood stabilizers such as lithium (with equal efficacy in the acute phase and the prevention of recurrent manic episodes). No consensus has been reached with regard to the treatment of bouts of acute mania in various parts of the world. Controlled clinical trials have, at last, provided irrefutable evidence of the activity of lithium, which has long been used alone, as well as that of divalproate or its derivatives and, to a lesser extent, carbamazepine. The new antipsychotic agents have more recently established their efficacy, especially aripiprazole, asenapine, quetiapine; olanzapine, risperidone, and ziprasidone (not sure where the paradox is). In Europe, haloperidol is still the reference substance used in clinical trials despite the fact that it is not officially indicated in the treatment of mania. In the USA, lithium, divalproate, or antipsychotics can be prescribed as first-line treatment. In Europe, lithium remains the first-line medication, whereas divalproate and atypical antipsychotic agents are used only as second-line therapy. Although both types of medication (antipsychotics, normothymic agents, and/or anticonvulsants) have proved to be clinically effective in the management of mania by reducing the mania scores overall, the same does not apply, however, to all symptoms of mania. Factorial approaches to mania have all shown that since there are several clinical forms of mania, several clusters of manic symptoms can be identified. Antipsychotic and normothymic agents and/or anticonvulsants do not appear to have the same effects on each of these identifiable clusters of symptoms, mainly psychotic features. We believe that it is vitally important for future clinical trials of mania treatment to focus on the treatment effect by adopting a factorial approach to characterization of the episode using an appropriate methodological structure. These questions highlight the uncertainty shrouding the very structure of manic episodes, namely that these are predominantly of a thymic or psychotic nature. The Europeans undoubtedly consider mania to be more of a thymic episode and prefer lithium as the first-line treatment, whereas the Americans believe that psychotic symptoms dominate and widely prescribe antipsychotic agents. However, from the standpoint of clinical trials currently available, even though antipsychotic agents are certainly effective in reducing the scores on the mania scales, it is not clear whether they can be considered purely as antimania treatments.